Assessment of deep brain stimulation candidacy during the COVID-19 pandemic: Lessons learned and future directions for neuropsychologists. Issue 1 (2nd January 2022) - Palmese, C. A.; Wyman-Chick, K. A.; Racine, C.; Pollak, L. E.; Lin, G.; Farace, E.; Tran, B.; Floden, D.; Bobholz, J.; Turner, T. H.; York, M. K.; ,
Abstract: Objective Neuropsychological assessment is integral to the pre-surgical deep brain stimulation (DBS) workup for patients with movement disorders. The COVID-19 pandemic quickly affected care access and shifted healthcare delivery, and neuropsychology has adapted successfully to provide tele-neuropsychological (teleNP) DBS evaluations during this time, thus permanently changing the landscape of neuropsychological practice. Method: In this paper, we discuss the lessons learned from the pandemic and we offer care management guidelines for teleNP and in-person evaluations of pre-DBS populations, with exploration of the feasibility of the different approaches for uninterrupted care access. Results: We summarize the strengths and weaknesses of these care models and we provide future directions for the state of clinical neuropsychological practice for DBS programs, with implications for broader patient populations. Conclusions: A better understanding of these dynamics will inform and educate the DBS team and community regarding the complexities of performing DBS neuropsychological evaluations during COVID-19 and beyond.